2021
DOI: 10.1002/hpm.3381
|View full text |Cite
|
Sign up to set email alerts
|

Projected private hospital expenditure in Ireland, 2018–2035: What role for demographics, cost, and Sláintecare?

Abstract: Despite private hospitals occupying an important role in the delivery of acute hospital care in Ireland, an understanding of future spending pressures on these services is limited.Particularly, a key dimension of Ireland's ambitious roadmap for healthcare reform (Sláintecare) seeks to remove private practice from public hospitals. However, to date, there has been no examination of how this reform could impact private hospital demand and expenditure, and ultimately, the capacity to treat public patients. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…The authors further note that most private patients in public hospital under the current system would likely become public patients under the proposed reform. Later work found that an increase in activity in private hospitals arising from the removal of private activity from public hospitals would have implications for capital investment and workforce requirements in private hospitals (Keegan et al, 2021). If the private hospital system fails to increase supply along with demand this could have implications for the public hospital system; for example, the National Treatment Purchase Fund purchases spare capacity in the private hospital system to treat people who have been on the public waiting lists for a long time.…”
Section: Integration Across Healthcare Sectorsmentioning
confidence: 99%
“…The authors further note that most private patients in public hospital under the current system would likely become public patients under the proposed reform. Later work found that an increase in activity in private hospitals arising from the removal of private activity from public hospitals would have implications for capital investment and workforce requirements in private hospitals (Keegan et al, 2021). If the private hospital system fails to increase supply along with demand this could have implications for the public hospital system; for example, the National Treatment Purchase Fund purchases spare capacity in the private hospital system to treat people who have been on the public waiting lists for a long time.…”
Section: Integration Across Healthcare Sectorsmentioning
confidence: 99%